Sustainable Development Goals (SDGs) and GDP : What National Accounts Bring to the Table - Alexander, Thomas (IMF Working Papers; Working Paper ;, 2018)
The Sustainable Development Goals (SDGs) adopted by the UN General Assembly in 2015 represent a new global consensus to end poverty, promote prosperity, and protect the environment. Goal 8 seeks to improve global resource efficiency in consumption and production and to decouple economic growth (GDP) from environmental degradation while Goal 12 focuses on sustainable consumption and production. While GDP does not capture these broader goals, we suggest that the System of National Accounts which incorporates but goes well beyond GDP, can be used for the measurement of these SDGs and to support policy. We construct a conceptual 'super balance sheet' with an expanded asset boundary to include durable consumer goods used to produce services, human capital, and access to resources such as clean water and air, education, health, and infrastructure, to produce an expanded household net worth.